2002
DOI: 10.1063/1.1504487
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen plasma-enhanced thermal donor formation in n-type oxygen-doped high-resistivity float-zone silicon

Abstract: The impact of plasma hydrogenation on the subsequent formation of thermal donors at 450 °C in n-type oxygen-doped high-resistivity float-zone silicon is investigated by a combination of electrical and spectroscopic techniques. It is shown that the increase of the doping concentration can be explained by the creation of two sets of donors. The first one is the classical double oxygen thermal donors (OTDs), which are introduced with a nearly uniform concentration profile across the sample thickness, while the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The latter reflect, in fact, the indiffusion of hydrogen, 4-6 suggesting a close correlation between hydrogen and the created shallow donors. It has been suggested in our previous work [4][5][6] that the STDH and OTD centers are created in silicon during hydrogenation and subsequent annealing, respectively.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The latter reflect, in fact, the indiffusion of hydrogen, 4-6 suggesting a close correlation between hydrogen and the created shallow donors. It has been suggested in our previous work [4][5][6] that the STDH and OTD centers are created in silicon during hydrogenation and subsequent annealing, respectively.…”
mentioning
confidence: 99%
“…3 Apart from the OTD centers, the creation of shallow thermal donors ͑STDs͒ in silicon due to plasma hydrogenation was also reported. [4][5][6] The diffusionlike spatial distribution of the excess free carriers suggests the involvement of hydrogen in the core structure of the STDs. These hydrogen-related STDs are hereafter labelled STDH.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that the presence of hydrogen in the detector fabrication process can enhance the generation of TDs [16]. Potential sources of hydrogen in detector manufacturing are Chemical Vapor Deposition (CVD) process steps using silane (Si 3 H 4 ) gas.…”
Section: Detector Processingmentioning
confidence: 99%